Geoeducation for Schoolchildren in Geopark Areas: Enhancing Awareness in Toba Caldera and Kenyir Geoparks - Siregar, Mahmul; Tarigan, Vita Cita Emia; Nasution, Zaid Perdana; Hanie, Meidina Zulfa; Adryansyah, Dony; Yulida, Devi (Mahadi: Indonesia Journal of Law, 2025)
Geoeducation or geoscience education is an important component in efforts to conserve nature and increase environmental awareness in geopark areas. One example of a geopark area in Indonesia is the Toba Caldera and Kenyir Geopark, the area has extraordinary geological value, as well as the potential to be used as an educational facility for school children. The main problem is that partners, especially schools, still view themselves as not being part of the geopark ecosystem. Therefore, community service activities need to be carried out to encourage partners to contribute, synergize, and benefit from the existence of the geopark. The problem statement that used are how is geo-education in the geopark area today, what is the role of schools/educational institutions in providing education in the geopark area, what steps can be taken to implement geo-education. This study uses a qualitative approach with a library research method. The type of literature study used is a narrative review. The implementation of geoeducation in geopark areas is an important strategy in environmental conservation efforts, strengthening local identity, and increasing awareness of the value of geological heritage from an early age. Schools and educational institutions play a central role in realizing contextual and enjoyable geosite-based education. For this reason, structured steps are needed, starting from identifying geosite potential, developing relevant teaching materials, teacher training, curriculum integration, to direct learning activities in the field. The success of geoeducation is also determined by the availability of adequate educational facilities and strong partnerships between geopark managers, government, schools, local communities, and higher education institutions.